When people estimate their personal intelligence who is overconfident? Who is accurate?. Issue 6 (29th June 2020) - Mayer, John D.; Panter, A. T.; Caruso, David R.
Abstract: Objective: We explore accurate self‐knowledge versus overconfidence in personal intelligence—a "broad" intelligence about personality. The theory of personal intelligence proposes that people vary in their ability to understand the traits, goals, plans, and actions of themselves and others. We wondered who accurately knew that they were higher in personal intelligence and who did not, and whether individuals with more accurate estimates were distinguishable from others in their psychological characteristics. Method: Three archival data sets were identified that included both self‐estimates and objective measures of personal intelligence: The measures were the Self‐Estimated Personal Intelligence scale and the Test of Personal Intelligence. Results: People who were over‐confident—overestimating their ability‐level of personal intelligence—were positive in their outlook and more sociable. People who provided the most accurate self‐estimates were higher in verbal and personal intelligences, more open, and more conscientious than others. Conclusions: People who were accurate about themselves have not been studied before in this context but may, for example, serve as the monitors and thinkers who help keep themselves and others reasonable and on track.